ANYTHING NEW UNDER THE SUN?! EXPLORING FURTHER AVENUES FOR WRITING ANOTHER COMMENTARY ON CHRONICLES - L C Jonker (Acta Theologica)
Over the past two decades, there has been an explosion of new commentaries on Chronicles. Scholars may justifiably ask whether there is anything new under the sun to investigate in another commentary on this book. Having been contracted to produce a commentary for the Old Testament Library series (as follow-up to Japhet’s majestic commentary), I am investigating some new avenues for this endeavour. Three potential areas are discussed: utilizing Achaemenid royal inscriptions and written records for the interpretation of Chronicles; revisiting theories on the composition of Chronicles, and bringing Chronicles and Pentateuchal studies into conversation with one another.